Survival of plant seeds in digestate storage—with and without prior anaerobic digestion - Hahn, Juliane; Plogsties, Vincent; Gerowitt, Bärbel; Heiermann, Monika (Frontiers in Energy Research, 2024)
Plant seeds from weeds and energy crops have the potential to survive anaerobic digestion (AD). Species able to form physically dormant, i.e., hardseeded (HS) seeds seem particularly resistant. However, it is not yet known to what extent the storage of the digestate after AD affects seed viability.Seed survival of five HS and six non-HS (NHS) species was investigated in three combinations of digestate storage (DS) and AD. First, untreated seeds were exposed to DS for maximum 12 weeks. To simulate short-circuited AD (ADshort) in biogas reactors, seeds were second subjected to labscale AD for one day before DS. Third, seeds of six species were exposed to full-scale AD (ADfull) followed by DS. Seed viability was determined using a combination of germination tests and tetrazolium staining. Viability was modeled as a function of exposure time.Seed viability was affected by DS, AD and AD+DS, but responses varied greatly between species and treatments. With increasing exposure time, viability decreased after a lag-phase, remained stable or even increased. The NHS species Cichorium intybus, Daucus carota, Echium vulgare, and Verbascum thapsus were most susceptible, with seed-killing close to 100% if DS was involved. The HS species Malva sylvestris, Melilotus albus and Melilotus officinalis were most resistant. They survived all treatments and were alive after 35 days of ADfull plus 3 months of DS. The resistance potential of the HS species Abutilon theophrasti and Malva alcea and of the NHS species Chenopodium album and two tomato varieties was intermediate. None of them survived ADfull+DS, but except A. theophrasti they were viable after ADshort+DS. With few exceptions, seed-killing by AD+DS was higher than that by AD alone.In conclusion, DS and AD+DS have the potential to reduce seed viability, but do not completely inactivate all species. Therefore, digestate can be contaminated with viable seeds and may lead to the spread of weeds, especially after a short-circuited AD. In order to ensure the sustainable use of digestates in terms of weeds, we recommend to investigate the factors contributing to seed inactivation and the quantity of seed introduced to AD.